DOES THE POLYMORPHISM OF GENES GSTT1, GSTM1, GSTR1 ON THE HEMODYNAMICS IN NEONATES WITH ASPHYXIA - Kovalova, O.M. (World of Medicine and Biology, 2012)
It was investigated GSTT1, GSTМ1, GSTР1 genes polymorphism in the newborns with asphyxia. It was determined the associations between GSTT1 deletion gene polymorphism and severe asphyxia in term newborns. It was shown the absence of significant differences in of heart rate, blood pressure, urine output during the first day of life in infants with functional and nonfunctional GSTT1, GSTM1, GSTR1 genes. The start dose of dopamine required to stabilize hemodynamics in newborns, as well as the duration of use were higher in newborns with genotype GG GSTR1 than in children with genotype AA GSTR1 and AG GSTR1.